Comparison of the on-hand and off-hand straight spikes in volleyball - Kan, Brian Luk-Ming (My University, 1980)
The purpose of this study was twofold: 1) to examine the differences between the on-hand side and off-hand side spikes in volleyball in terms of velocity and accuracy, and 2) to evaluate the relationship of the angle of projection with velocity in each spike. The subjects (N=12) were members of 1979-80 University of Alberta Volleyball Team. The research design employed a repeated measures technique with two variables, the on-hand and off-hand spikes. Subjects were required to perform 20 straight spikes for each technique. The velocity and the angle of projection data for each trial were obtained by cinematographical analysis. Accuracy scores were collected by direct recording after each trial. A correlated t test was used to determine the differences in velocity and accuracy between the on-hand and the off-hand spikes. A Pearson Product-moment Correlation Coefficient was used to assess the relationship between the velocity and the angle of projection of each spiking technique for each subject. A further correlated t test was used to determine differences in that relationship between the on-hand and off-hand spikes. The results indicated that the differences between the on-hand and off-hand spikes, in terms of velocity and accuracy, were significant (P < .05). There was no relationship between the velocity and the angle of projection for the on-hand spike but a low significant relationship was observed for the off-hand spike. The difference in relationship of velocity and angle of projection between both spiking techniques was not significant. Several recommendations for future researches in this area were offered.
Keywords: Volleyball